Assessment of coastal water quality of Ninh Binh province - Trang, Cao Thi Thu; Thao, Nguyen Van; Kha, Pham Thịi; Nam, Le Van; Bach, Nguyen Van; Ha, Nguyen Thi Thu (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents the results of investigation on water quality in Ninh Binh coastal area in 2015. The results show that the risk quotient of water quality of the area was 0.34, indicating the water was safe for aquatic life. However, for individual water quality parameter, the coastal water of Ninh Binh was contaminated by TSS, ammonium and arsenic; water faced the risk of deficiency of dissolved oxygen. The remaining water quality parameters (nitrite, phosphate, cyanide, oil and grease, coliform, Cu, Pb, Zn, Cd, Hg and organochlorinated pesticides) are safe for aquatic life. As spatial distribution, the concentration of pollutants in water is lower at depth > 15 m. In the rainy season, the water quality tends to decrease compared to the dry season.